On-farm Validation of IPM Module in Tomato in North West Himalayas - Hooda, K.S.; Bhatt, J.C.; Jhosi, D.; Sushil, S.N.; Singh, S.R.K.; Siddiqie, S.S.; Choudhary, B. (Indian Journal of Extension Education, 2009)
This study was conducted in mind- hills of Uttarakhand situated in North West Himalayas (NWH). The IPM module (seed treatment: drenching and root dip @ 1% with Trichoderma harzianum, mancobez sprays @ 0.25 % and HaNPV @ 250 LE/ ha (two spray) installation of pheromone trap, staking & removal of lower leaves, 9â€ from the soil and one row of marigold after 16 lines of tomato) was validated at farmers fields . Higher emergence of tomato seedling ( 65- 80%) was recorded in bioagent treated seed at raised beds than untreated seed in flat bed traditionally (40%) followed under farmers practice. Pre-emergence rot in the nursery was controlled to the extent of 41.7â€“66.7 percent over untreated and flat bed system. On an average 60 percent control of early blight was achieved with IPM practices compared to non-IPM practices. Buckeye rot was immensely reduced (85.7 %) with staking and removal of lower leaves followed by single spray of mancozeb over unstaked and unsprayed tomato plants emphasizing the significant role of staking in the control of this disease. Staking HaNPV and trap crop of marigold recorded 5 per cent borer attack compared to 18 per cent in untreated fields giving 72.2 per cent control of fruit borer. The integrated crop management along with IPM module contributed greatly in attaining economically higher yield than traditional practices. Thus, adoption of IPM module is an economically viable and profitable venture in NWH for healthy tomato production as revealed by B:C ratio obtained by the participatory farmers.